Developing a Gesture-based AR Exhibit: Differently-Guided Experiences for Complex Conceptual Learning in Science - Min-Hwi Seo; Hyo-Jeong So (Educational Technology & Society, 2022)
The purpose of this research was to design and evaluate the efficacy of a gesture-based exhibit with augmented reality (AR) for understanding complex scientific concepts. In particular, this study focuses on the effect of differently guided conditions in a gesture-based AR. We first present the design and development of a gesture-based AR exhibit about the conductor resistance phenomenon. An experiment was conducted to examine the effect of guided and unguided experiences on complex conceptual learning. In the experiment, 40 participants between 15 and 17 years-old were randomly assigned to either the guided (visual and docent explanation) or unguided condition. Their understanding of complex concepts was measured through the pre-test and post-test. The results indicate that while the participants increased cognitive understanding after experiencing the gesture-based AR exhibit, there was no significant difference between the two conditions. This may imply that the provision of extra guidance does not necessarily lead to better conceptual learning. In conclusion, this study provides some implications concerning the design of new types of immersive exhibits in museum contexts.